Methodical aspects of work on the qualification work of future teachers of fine arts (Pedagogy of Higher and Secondary Education, 2009)
In article process of performance of qualifying work is considered, motives and methods of creation of a picturesque composition are analyzed.
Keywords: composition; degree task; methods; creativity